2008
DOI: 10.3748/wjg.14.5851
|View full text |Cite
|
Sign up to set email alerts
|

FR167653, a p38 mitogen-activated protein kinase inhibitor, aggravates experimental colitis in mice

Abstract: AIM:To investigate the effects of FR167653 on the development of dextran sulfate sodium (DSS)-induced colitis in mice. METHODS: BALB/c mice were fed rodent chow containing 3.5% (wt/wt) DSS. The recipient mice underwent intra-peritoneal injection of vehicles or FR167653 (30 mg/kg per day). The mice were sacrificed on day 14, and the degree of colitis was assessed. Immunohistochemical analyses for CD4 + T cell and F4/80 + macrophage infiltration were also performed. Mucosal cytokine expression was analyzed by RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It has been reported that an intraperitoneal injection of the p38 MAPK-specific inhibitor FR167653 aggravated 3% DSS-induced colitis [35]. This suggests that activation of the p38 MAPK pathway is a protective reaction against the excess inflammation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been reported that an intraperitoneal injection of the p38 MAPK-specific inhibitor FR167653 aggravated 3% DSS-induced colitis [35]. This suggests that activation of the p38 MAPK pathway is a protective reaction against the excess inflammation.…”
Section: Discussionmentioning
confidence: 95%
“…P38 MAPK is a class of mitogen-activated protein kinases responsive to stress stimuli, such as cytokines, ultraviolet irradiation, heat shock, and osmotic shock, and is involved in cell differentiation and apoptosis. It has been reported that an intraperitoneal injection of the p38 MAPK-specific inhibitor FR167653 aggravated 3% DSS-induced colitis [35] . This suggests that activation of the p38 MAPK pathway is a protective reaction against the excess inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Hollenbach et al . found that inhibition of p38 MAPK was able to drastically reduce colonic NF-kB activity with a consequent improvement of intestinal lesions in a murine model [ 27 ], whereas in other studies inhibition of p38 MAPK activation worsened the course of 2,4,6-trinitrobenzenesulfonic (TNBS) acid or dextran sulphate sodium (DSS) induced colitis [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, epidermal growth factor receptor (EGFR)-induced intestinal epithelial cell migration depends on MAPKp38 signaling mediated by the family of Src kinases [29,30]. Intestinal ischemia/reperfusion injury leads to rapid activation of MAPKp38 signaling in intestinal epithelial cells [31,32], and inhibition of MAPKp38 signaling exacerbates DSS-induced colitis, as well as TNBS-induced weight-loss in mice [33,34]. Activation of MAPKp38 signaling by TGF-β is crucial in inducing epithelial to mesenchymal transformation, one of the deciding steps in early epithelial restitution [35,36].…”
Section: Wound-induced Mapkp38 Signalingmentioning
confidence: 99%